Whipple's in the valleys: a case of Whipple's with thrombocytopenia and endocarditis. Issue 5 (23rd January 2014) - Loughran, Dafydd; Beale, Lee; Lodge, Freya; Habboush, Husni; Stock, David
Abstract : Introduction: This case report details the second described case of Whipple's disease-related thrombocytopenia in the medical literature. Whipple's disease is a rare multisystem infection caused by the actinomycete Tropheryma whipplei, first described by George Whipple in 1907. The key clinical manifestations are weight loss, diarrhoea and malabsorption, but arthralgia and endocarditis are also well described. Case presentation: A 62-year-old Caucasian female presented with weight loss, anaemia and behavioural changes but denied any abdominal symptoms. Thrombocytopenia subsequently developed rapidly. Bone marrow examination showed abundant megakaryocytes in keeping with peripheral platelet sequestration. In addition, there was significant polyclonal plasmacytosis. She was also found to have a 1.6 cm tricuspid vegetation. The diagnosis was confirmed by presence of foamy macrophages on duodenal biopsy, positive periodic acid-Schiff staining and visualisation of T whipplei actinomycetes on electron microscopy. Tissue PCR performed mid-treatment showed traces of T whipplei DNA. The infection was treated with a 2-week intravenous course of ceftriaxone followed by 12 months of oral co-trimoxazole. The thrombocytopenia and anaemia resolved rapidly with antibiotic therapy, her behaviour returned to normal and she remains clinically well. Conclusions: This report confirms the association of thrombocytopenia with Whipple's disease, likely due to peripheral platelet sequestration, which resolves rapidly with treatment. In patients with a long history of unintended weight loss, Whipple's disease is a rare but important differential diagnosis as it is ultimately fatal if left untreated.